Thermal and thermo-hydraulic analysis of arc shaped rib roughened solar air heater integrated with fins and baffles. (1st March 2019) - Saravanakumar, P.T.; Somasundaram, D.; Matheswaran, M.M.
Highlights: SAH with arc shaped rib roughened absorber plate integrated fins with baffles have better performance. Maximum enhancement in thermal efficiency and effective efficiency is 28.3% and 27.1% respectively. Correlation for effective efficiency is developed as a function of design and flow conditions. Abstract: Present study deals with thermo hydraulic performance enhancement of solar air heater (SAH) with various design configurations. Analytical modeling is carried out to study the effect of absorber plate integrated with arc shaped rib roughened barrier with fins and baffles on thermal and effective efficiency of SAH. Variations of flow factors such as Reynolds number and temperature rise parameter with reference to baffle design parameters are presented. The proposed SAH improves the energy and effective efficiency by 28.3% and 27.1% compared with arc shape rib roughened solar air heater. From the results, it is also concluded that lower baffle width and length values provide maximum effective efficiency at higher mass flow rates. Further, the correlations as a function of Reynolds number, baffle width, length and number of fins is developed for predicting the values of effective efficiency. Thereafter, a plot is developed for comparing analytical effective efficiency with predicted effective efficiency and it is found that the averaged deviation of 13%. This present mathematical model for proposed SAH is validated with models available in the literature.